Computational insights of double perovskite X2CaCdH6 (X = Rb and Cs) hydride materials for hydrogen storage applications: A DFT analysis - Azeem, Waqar; Hussain, Shoukat; Shahzad, Muhammad Khuram; Azad, Fahad; Khan, Gul; Tirth, Vineet; Alqahtani, Hassan; Algahtani, Ali; Al-Mughanam, Tawfiq; Wong, Yew Hoong (International journal of hydrogen energy, 2024)
Perovskite materials play a backbone role in materials science to investigate various applications including photocatalytic, photovoltaic, and hydrogen storage. Hydrogen storage is a modern technique to fulfill energy consumption and demands. We inspect the structural, hydrogen, electronic, optical, and thermodynamic properties of X2CaCdH6 (X = Rb and Cs) perovskite substances for hydrogen (H2) storage applications. The research shows substances have 225 Fm3m cubic natures and 40 atoms. The formation and cohesive energies of the examined structures show that X2CaCdH6 (X = Rb and Cs) substances may be produced and are thermodynamically stable. Electronic characteristics indicate that substances are semi-metallic, with correspondingly indirect bandgap Eg energies of 2.13 eV and 2.30 eV. The mechanical stability (Born stability), brittle (B/G = 1.22, 1.15 and α = 0.17, 0.18), hard (6.255, 5.481), and anisotropic (0.278, 0.171) of the X2CaCdH6 (X = Rb and Cs) perovskite substances are demonstrated by the examined elastic values. The Debye temperature ΘD (289.395, 320.837)K, melting temperature Tm (646.961, 650.714)K, acoustic velocities (vm, vl, vt) m/s, minimum thermal conductivity Kmin (0.63, 0.75) (W/mK), and Grüneisen parameter (18.121, 19.521) of substances are also computed by investigating their thermodynamic characteristics. Cs2CaCdH6 and Rb2CaCdH6 have gravimetric ratios of 1.39 wt% and 1.69 wt%, correspondingly. Our findings shed light on using double perovskites X2CaCdH6 (X = Rb and Cs) as a hydrogen (H2) storage substance. •CASTEP code is used to study the physical properties of X2CaCdH6(X = Rb and Cs) compounds.•The compounds under study are optimized in the cubic structure.•Band gaps verify the semiconductor characteristics of said compounds.•These hydrides are thermally and mechanically stable.•Results depict that compounds is better for H2 storage applications.